Study on the relative collection efficiency of large area PMTs. (19th May 2021) - Ma, L.; Xia, J.; Qian, S.; Gao, F.; Huang, G.; Wu, Q.; Sun, J.; Ren, L.; Si, S.; Zhu, Y.; Wang, Z.
Abstract: The relative collection efficiency (CE) of 20-inch Photomultiplier Tubes (PMTs) cannot be measured directly, but it can be obtained by the quantum efficiency (QE) of the photocathode and the relative detection efficiency (DE) of the PMTs. The measurements of relative CE and its spherical uniformity of the 20-inch PMTs have been introduced in this manuscript, and the difference in performance between Microchannel-Plate PMT (MCP-PMT) and Dynode-PMT were shown. The CE performance for 20-inch PMTs are given and the batch test results of CE for MCP-PMTs and Dynode-PMTs are compared at the end of this manuscript.